1997
DOI: 10.1016/s0022-5347(01)64882-1
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Vesicoureteral Reflux Guidelines Panel Summary Report on the Management of Primary Vesicoureteral Reflux in Children

Abstract: For most children the panel recommended continuous antibiotic prophylaxis as initial treatment. Surgery was recommended for children with persistent reflux and other indications, as specified in the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
108
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(110 citation statements)
references
References 8 publications
2
108
0
Order By: Relevance
“…The well-known association between VUR and UTI has led to the concept that VUR plays a pathogenetic role in the development of UTI, acute pyelonephritis and renal scars. Children with VUR are usually given prophylactic antibiotics 9 10. In our subgroup analysis, we found that long-term antibiotic prophylaxis in children with VUR was not related to a decrease in recurrent symptomatic UTI.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The well-known association between VUR and UTI has led to the concept that VUR plays a pathogenetic role in the development of UTI, acute pyelonephritis and renal scars. Children with VUR are usually given prophylactic antibiotics 9 10. In our subgroup analysis, we found that long-term antibiotic prophylaxis in children with VUR was not related to a decrease in recurrent symptomatic UTI.…”
Section: Discussionmentioning
confidence: 60%
“…Renal involvement in the acute phase of infection and subsequent scarring may lead to the development of chronic renal impairment and hypertension 7 8. Long-term antibiotic prophylaxis has for many years been given to children at risk for UTI, especially those with vesicoureteric reflux (VUR), a condition present in approximately 30–40% of children with UTI 9 10. However, this recommendation is based on expert opinion rather than clear scientific evidence.…”
Section: Introductionmentioning
confidence: 99%
“…The upper age was subsequently shown to be about 4 years by using dimercaptosuccinic acid (DMSA) scans which detect scars immediately they occur 11. It was widely assumed (including by the authors at the time) that as well as reflux tending to resolve with time,12 human kidneys must also mature in such a way that they lose their vulnerability to scarring by 4 years of age. However, this view has now been challenged in a way which, if sustained, will have major implications.…”
mentioning
confidence: 99%
“…Surgical reimplantation has general risks of anaesthetic use, postoperative infection, and ureteric obstruction. 8 There is increasing concern about the development of antibiotic resistant bacteria following long term antibiotic use. 9 Quantifying these potential harms is problematic.…”
mentioning
confidence: 99%